A CORRELATION BETWEEN INTRAVESICLE PROSTATIC PROTRUSION AND PROSTATE VOLUME IN PATIENTS PRESENTING WITH ACUTE URINARY RETENTION – A DESCRIPTIVE STUDY - GAURAV BAJPAI; SAHIL GAMBHIR; BHERU SINGH HARIYAWAT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to study the prevalence of significant intravesical prostatic protrusion (IPP) in patients presenting with acute urinary retention (AUR) due to benign prostatic hyperplasia and to study the correlation between IPP and prostatic volume. Methods: Forty men between 45 and 85 years of age, who presented with AUR. Initial assessment included detailed clinical history, International Prostate Symptom Score, and Quality of Life assessments, and a transabdominal ultrasonogram to measure Prostate Volume (PV) and IPP. IPP is measured by drawing a line corresponding to bladder base on a sagittal view and perpendicularly measuring the distance from the bladder base to the greatest protrusion of the prostate into the bladder. Patients with IPP >10 mm were taken to have significant IPP and those ≤10 mm were taken to be insignificant. Statistical analysis included descriptive analysis and Pearson’s correlation coefficient. Results: Of the 40 patients in our study with resented with AUR, 21 patients (52.5%) had significant IPP. Mean IPP was 11.3 mm with a standard deviation of 5.49 mm. All patients with significant IPP had a severe IPPS grade. IPP had a statistically significant correlation with PV. Conclusion: The IPP assessed by transabdominal ultrasound can be used to direct appropriate patients to more aggressive treatment strategies like surgery.